Role of C1q/TNF-Related Protein 6 for the Evaluation of Coronary Heart Disease Associated with Type 2 Diabetes - Li M; Zhou S; Feng Z; Zhang C (Dove Medical Press, 2024)
Mianxian Li,1,* Shuru Zhou,2,* Zexiong Feng,1,* Chi Zhang1 1Department of Cardiology, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People's Republic of China; 2The Aoyang Cancer Institute, Affiliated Aoyang Hospital of Jiangsu University, Suzhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Chi Zhang, Email zhangchi13@suda.edu.cnObjective: Coronary artery disease (CAD) and type 2 diabetes (T2DM) are closely associated with increased rate of death. C1q/TNF-related protein 6 (CTRP6) is a novel adipocytokine which plays an important role in glucose and lipid metabolism. Little is known about the function of CTRP6 in CAD and T2DM patients. Herein, we aimed to study the association of CTRP6 level with CAD and T2DM.Methods: This study included 51 CAD, 44 CAD+T2DM and 65 non-CAD+T2DM patients from Affiliated Aoyang Hospital of Jiangsu University. Serum CTRP6 concentrations were detected by ELISA. Multiple logistic regression was used to analyze the association of serum CTRP6 with CAD and T2DM.Results: Serum CTRP6 concentrations were significantly lower in CAD patients than controls. However, there is no significant statistical difference between CAD+T2DM patients and non-CAD+T2DM patients. Serum CTRP6 was negatively correlated with low-density lipoprotein cholesterol (LDL-C) (ρ=− 0.2769, p=0.028) in controls. Serum CTRP6 was positively correlated with age (ρ=0.4121, p=0.0027), systolic blood pressure (SBP) (ρ=0.4012, p=0.0035), Creatinine (ρ=0.3295, p=0.0194), uric acid (UA) (ρ=0.3386, p=0.0162), and left ventricular end diastolic diameter (LVD) (ρ=0.4277, p=0.0042) and negatively correlated with ejection fraction (EF) (ρ=− 0.3237, p=0.0342) in CAD patients. Serum CTRP6 was negatively correlated with high-density lipoprotein cholesterol (HDL-C) (ρ=− 0.3164, p=0.0387) in CAD+T2DM patients. Multiple logistic regression showed that the decrease of CTRP6 was significantly related to the increased prevalence of CAD. What is more, CTRP6 increased prevalence of T2DM in CAD patients.Conclusion: Lower serum CTRP6 could be a risk factor of CAD. However, higher circulating CTRP6 associated with the increased prevalence of T2DM in CAD patients.Keywords: CTRP6, coronary artery disease, type 2 diabetes, adipokine, CTRP, risk factor